SAT0599 Autoimmnune Disease in Acute Coronary Syndromes. Clinical Implications. (15th July 2016) - Lozano-Rivas, N.; Marras-Fernández Cid, C.; Flores-Blanco, P.; Pastor-Perez, F.J.; Linares, L.F.; Martinez-Angosto, F.A.; Martínez-Ferrin, J.; Manzano-Fernández, S.
Abstract : Background: Patients with autoimmune diseases (AID) have a high burden of cardiovascular disease leading to premature morbidity and mortality 1 . But it is unclear if it is due to a higher prevalence of cardiovascular disease, to a worse case fatality or to a different management after an index event. Objectives: The aim of the study is to assess the prevalence of AID in patients with acute coronary syndrome (ACS), the management and prognostic implications. Methods: The study included consecutive patients admitted after ACS from January 2011 to May 2014. For AID patients, in-hospital management and ACS presentation was compared to non-AID patients. We also compared in-hospital and 1-year major adverse events (MACE): death, recurrent myocardial infarction, stroke and major bleeding, between groups. The percentage lost to follow-up was <1%. Results: Of 964 patients, 53 had AID (5.5%): 11 rheumatoid arthritis, 9 inflammatory bowel disease, 7 ankylosing spondylitis, 7 psoriatic arthritis, 5 polymyalgia rheumatica, 4 systemic lupuserythematosus and 10 miscellanea. Mean evolution of the disease was 14±3 years. No significant differences were found in clinical and demographics characteristics between groups except for a higher percentage of previous stable coronary heart disease in non-AID patients. Compared to non-AID patients, AID patients had similar clinical ACS presentation and no differences were found with respect to revascularization strategies or medical treatment at discharge. Overall there were 207 MACE (69% during hospitalization): 108 deaths, 52 recurrent myocardial infarctions, 19 ischemic strokes and 28 major bleedings. The two groups had comparable rates of MACE both during hospitalization (9.6% vs 12.2%, p=0.58) and at 1 year (26.4% vs 19.1%, p=0.19), AID vs non-AID respectively. The presence of AID was not associated with increased in-hospital mortality (OR 1.1, 95% CI 0.4 to 3.3) but it was a risk factor for higher 1-year crude mortality (OR 2.2, 95% CI 1.1 to 4.4), with a trend to higher 1-year mortality after multivariable adjusting (OR 1.7, 95%CI 0.8 to 3.9). Conclusions: The presence of AID did not change ACS presentation and clinical management. Moreover it is not independently associated with worse outcomes during hospitalization although there is a trend to higher 1-year mortality. References: Symmons DP, Gabriel SE. Epidemiology of CVD in rheumatic disease, with a focus on RA and SLE. Nat Rev Rheumatol. 2011 May 31;7(7):399–408 Disclosure of Interest: None declared